Pathology and Molecular Diagnosis of Velogenic Viscerotropic Newcastle Disease Virus in Desi Chickens of Chhattisgarh - Sonkusale, Prashant M.; Ghosh, Ratan C.; Giri, Devesh kumar; Kumar, Vivek; Shukla, Neha; Gumasta, Poornima; Bisen, Savita (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Newcastle disease (ND) is an economically important viral disease of birds caused by Avian Paramyxovirus type 1. In the present study, mortality of 56.50 to 74.50% due to ND in four desi chickens farms located in Durg district of Chhattisgarh was noticed which were not vaccinated against NDV  The gross and histopathological lesions were suggestive of viscerotropic velogenic form of ND. Tissue samples of trachea and lung collected from 18 desi birds belonging to four desi flocks were confirmed as ND by RT-PCR amplification of 535 bp of fusion protein gene of NDV. In the present study, velogenic viscerotropic NDV was confirmed in all four desi flocks by gross and microscopic examination and RT-PCR assay.
Keywords: Pathology; Molecular Diagnosis; Chhattisgarh; Virus; Desi Chickens